2017
DOI: 10.1038/srep45963
|View full text |Cite
|
Sign up to set email alerts
|

Association of glucose-6-phosphate dehydrogenase deficiency and malaria: a systematic review and meta-analysis

Abstract: Glucose-6-Phosphate Dehydrogenase (G6PD) deficiency overlaps with malaria endemicity although it predisposes carriers to hemolysis. This fact supports the protection hypothesis against malaria. The aim of this systematic review is to assess the presence and the extent of protective association between G6PD deficiency and malaria. Thirteen databases were searched for papers reporting any G6PD alteration in malaria patients. Twenty-eight of the included 30 studies were eligible for the meta-analysis. Results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
76
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 47 publications
8
76
0
2
Order By: Relevance
“…Previously we studied the Class III G6PD A+ variant (single nucleotide substitutions) and also characterized it as a comparative variant with respect to G6PD San Luis Potosi, in which the single nucleotide substitutions are located in the same 126 amino acid codon. As previously noticed, the G6PD A+ variant was related in an asymptomatic G6PD deficiency form [6]. This mutation results in a change of adenine by guanine (A→G) in nucleotide (nt) 376 of the G6PD gene and is located in exon 5, with a change on the asparagine by aspartic acid (Asn→Asp) amino acid residue in the 126 position of the three-dimensional (3D) structure (Figure 1).…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Previously we studied the Class III G6PD A+ variant (single nucleotide substitutions) and also characterized it as a comparative variant with respect to G6PD San Luis Potosi, in which the single nucleotide substitutions are located in the same 126 amino acid codon. As previously noticed, the G6PD A+ variant was related in an asymptomatic G6PD deficiency form [6]. This mutation results in a change of adenine by guanine (A→G) in nucleotide (nt) 376 of the G6PD gene and is located in exon 5, with a change on the asparagine by aspartic acid (Asn→Asp) amino acid residue in the 126 position of the three-dimensional (3D) structure (Figure 1).…”
Section: Introductionmentioning
confidence: 68%
“…G6PD deficiency, a hereditary genetic defect, is the most common enzymopathy in humans, affecting more than 400 million people worldwide, indicating a global prevalence of 4.9% [4]. The prevalence of G6PD deficiency correlates with the geographical distribution of endemic areas malaria, and has been postulate that G6PD deficiency is an adaptative response as protection against severe forms of P. falciparum malaria and that inheriting the G6PD deficiency gene reduces the severity of malaria infection [5][6][7][8]. The clinical spectrum of this disease includes patients with no symptoms to those with neonatal hyperbilirubinemia resulting in kernicterus (which can be fatal), episodes of acute hemolysis due to the ingestion of exogenous agents (drugs, food, or infectious agents), or chronic nonspherocytic hemolytic anemia [3,9].…”
Section: Introductionmentioning
confidence: 99%
“…Hemoglobinopathies (mainly HbAE or HbEE), and possibly, glucose-6-phosphate dehydrogenase (G6PD) deficiency, which are highly prevalent in Southeast Asian populations, might also have a role. These disorders alter the redox state of RBCs, helping to protect against severe forms of malaria, and possibly influencing the action of drugs such as ART derivatives that are suspected to act in part by increasing oxidative stress in a parasitized cell 4954 .…”
Section: Multidrug Resistance (Mdr)mentioning
confidence: 99%
“…Similarly, both α−/αα and α−/α− thalassaemia reduce the risk of severe malaria by 20-40% [5][6][7]. The association between glucose-6-phosphate dehydrogenase [G6PD] deficiency and severe malaria is less clear [4,8]. Some studies reported that G6PD protects both heterozygous females and hemizygous males from severe malaria [9], others reported protection for only hemizygous males [10], and others reported no protection [8].…”
Section: Introductionmentioning
confidence: 99%
“…The association between glucose-6-phosphate dehydrogenase [G6PD] deficiency and severe malaria is less clear [4,8]. Some studies reported that G6PD protects both heterozygous females and hemizygous males from severe malaria [9], others reported protection for only hemizygous males [10], and others reported no protection [8]. Mechanisms through which these variants confer protection appear to be complex and may include restriction of red blood cell invasion and intracellular growth, increased destruction of parasitized red cells, and improved cell mediated and humoral immune responses [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%